ARTIFICIAL INTELLIGENCE TOOLS IN ENVIRONMENTAL ADVOCACY AND COMMUNICATION: A SYSTEMATIC REVIEW (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the role of artificial intelligence (AI) tools in environmental advocacy and communication, synthesizing current research on AI applications for promoting pro-environmental attitudes and behaviors. The study analyzes recent experimental and design-based research published between 2025-2026, focusing on three primary AI applications: generative AI as information sources, AI-powered chatbots for community engagement, and AI-driven content creation and analysis tools. Findings reveal that AI-generated environmental messages can significantly enhance awareness of consequences, moral obligation, and attitudes toward environmental problems, with effectiveness comparable to traditional media sources . AI-powered chatbots demonstrate particular promise in democratizing environmental reporting and creating emotional connections with nature through anthropomorphic design. However, research also indicates that hyper-personalized "nano-targeting" approaches may risk audience polarization rather than broad persuasion. The article concludes with practical recommendations for environmental communicators and identifies directions for future research.